Severe conduct problems in adolescence and risk of schizophrenia in early adulthood - Manninen, Marko; Latvala, Reetta; Torniainen‐Holm, Minna; Suvisaari, Jaana; Lindgren, Maija (Early intervention in psychiatry, 2019)
Aim Reform school (RS) is a foster care institution for adolescents with severe conduct problems. Both instability of early rearing environment and severe conduct problems in adolescence may associate with later psychotic disorders. We studied whether the risk of schizophrenia in adulthood is elevated in RS adolescents, and whether it is related to the age at first foster care placement or placement instability. Methods Adult age schizophrenia spectrum disorder data from RS subjects (N = 1099) were compared to a comparison group matched by age, sex, and place of birth (N = 5437) in a register based follow‐up study, with up to 23 years follow‐up time. Schizophrenia was also predicted with chosen placement factors. Cox proportional regression model was used in the analysis. Results RS subjects had an 8‐fold (HR = 7.82, 95% CI 5.63‐10.87) risk of schizophrenia compared to the comparison group. RS subjects also had an earlier age of schizophrenia onset. RS cohort, gender, placement instability, or age during the first out‐of‐home placement did not predict later schizophrenia. Conclusions Adolescents with severe conduct problems are a specific high‐risk group for later schizophrenia. The risk manifests early, which compromises the pathway to the adult well‐being. Specialized screening procedures for psychosis risk should be implemented in the standard clinical procedures when working with adolescents with severe behaviour problems, and early intervention programs should be available.